MORPHOLOGICAL SIGNIFICANCE OF BONE ATROPHY FOR TOPOGRAPHIC FEATURES OF THE LEFT MANDIBULAR CANAL - Oshurko, A.P.; Oliinyk, I.Yu.; Kuzniak, N.B. (World of Medicine and Biology, 2021)
In clinical practice, when analyzing computed tomography studies, the attention of dental surgeons is attracted by topographic and anatomical changes in the mandibular canal concerning the bilateral loss of molars, which cause bone atrophy, even in individuals without obvious effects of somatic pathology or environmental conditions. In the study, we used the standardized CT software “Vatech original 2020”. It was found that while preserving the dentition rows, the topography of the left mandibular canal approaches its lingual surface on the ≈ 1.5 mm; the canal is delimited only by the cortical layer of bone tissue. When the first molars are lost, the mandibular canal is displaced by ≈ 3.1 mm relative to the outer edge of the buccal surface. With acquired terminal dentition defects, “morphological transposition” acquires ≈4.9 mm relative to the buccal surface with a distance to the middle ≈3.0 mm from the edge of the lingual surface of the mandible. The presented description of the absolute morphometric values of the mandibular canal by its average number improves the visual perception of its topographic features with the occurrence of a neurovascular bundle in it and remains a sign drawing up a treatment plan and choosing rehabilitation methods.